Penguatan Karakter Religious Peserta Didik Melalui Pembelajaran Pendidikan Agama Islam - Nova Maulidia; Nabila Norma Okta Zakiya; Khumaidatur Rohimah; Saely Salwa Zuhairok; Slamet Slamet (CV. Lentera Literasi Indonesia, 2026)
This study aims to describe and analyze in depth how Islamic Religious Education (PAI) learning can serve as an effective medium for strengthening the religious character of students. The religious character in this context includes values such as honesty, discipline, responsibility, tolerance, and social care, all of which are derived from Islamic teachings. The research employed a qualitative method with a case study approach conducted at a junior high school with an outstanding Islamic Religious Education program. Data were collected through observations, in-depth interviews with PAI teachers, students, and the school principal, as well as document analysis. The results indicate that PAI learning, which integrates both intracurricular and extracurricular activities and is supported by a conducive school environment, effectively fosters and develops the students’ religious character in a significant manner.